2010
DOI: 10.1111/j.1553-2712.2010.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Emergency Severity Index Triage Instrument for Identifying Elder Emergency Department Patients Receiving an Immediate Life‐saving Intervention

Abstract: Objectives: The study objective was to determine the sensitivity and specificity of the Emergency Severity Index (ESI) triage instrument for the identification of elder patients receiving an immediate life-saving intervention in the emergency department (ED). Methods:The authors reviewed medical records for consecutive patients 65 years or older who presented to a single academic ED serving a large community of elders during a 1-month period. ESI triage scores were compared to actual ED course with attention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 20 publications
4
90
1
3
Order By: Relevance
“…Tanabe et al confirmed the high reliability of five-level triage, and reported a high reliability for it (Kappa = 0.89) (13). Some studies reported that ESI is a valid and reliable method for better allocation of resources and better classification of patients to get appropriate treatment (14,15). In the first moment of the patient's admission to ER, demographic data (age, sex, date, time of patient's referral and cause of admission) were obtained.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Tanabe et al confirmed the high reliability of five-level triage, and reported a high reliability for it (Kappa = 0.89) (13). Some studies reported that ESI is a valid and reliable method for better allocation of resources and better classification of patients to get appropriate treatment (14,15). In the first moment of the patient's admission to ER, demographic data (age, sex, date, time of patient's referral and cause of admission) were obtained.…”
Section: Methodsmentioning
confidence: 95%
“…According to Kariman et al, the sensitivity of ESI in identification of old patients who should receive lifepreserving interventions was low (5). As Platts-Mills et al reported, this can be related to the fact that nurses did not triage patients directly; they only referred to the patient's past medical history (15). Although the majority of patients experienced correct triage, but 12% experienced undertriage and 11.1% experienced overtriage.…”
Section: Discussionmentioning
confidence: 99%
“…65 It is also possible that the enrollment process enriched the sample with patients who were admitted because patients who were flagged for discharge were not eligible, and patients who anticipated going home might have been more reluctant to participate in a study that might prolong their ED visit. Consistent with this, 21 patients were not screened because they were flagged as discharged prior to being screened, 18 patients refused the screener, and three patients were eligible but declined participation because they thought it would take too much time (Figure 1).…”
Section: Limitationsmentioning
confidence: 99%
“…32,33 Although experts hypothesize about the essential components of a high-quality geriatric ED, 34,35 we provide early research to systematically identify and qualitatively characterize the existence, locations, and features of geriatric EDs across the United States. These descriptive details will be essential in understanding the variety of services offered and evaluation methods.…”
mentioning
confidence: 99%